The impact of transformational and transactional leadership style on job satisfaction among the employees in student affairs division (HEPA) University of Malaya / Nurul Syakinah Othman - Othman, Nurul Syakinah (Faculty of Business and Management, 2018)
Leadership is the most important thing in the company which is a leader will lead the employees or followers. This study was conducted at Student Affair Division (HEPA), University of Malaya. The objective of this study is to find out which leadership is significant to the employees whether Transactional or Transformational leadership style. Leadership is very important to employees because the leader will help and guide the employees, sharing the vision and also provide information to the employees. The statement of problem for this research is transformational leadership style is when a leader is loss of inspiration. Leaders will give inspire to the team how to achieve and success, and also encourage them to make the commitment require to work. Other than that, transactional leadership style is when the leader is too obsessed with the perfection of their task; the employee will get a bad impact on it. Questionnaire were gives 41 respondents to complete the survey. Data were run by using SPSS and the result of the study will be used for the company in the future. In the plan data analysis, I used Pearson correlation to show all the result and explain the objective.